Sorption of selected dyes under dynamic conditions - Ewa Okoniewska (Desalination and Water Treatment)
Dyes are widely used in various industries. These include the textile, cosmetics, food, paper and plastics industries. The textile industry, where dyes play a predominant role, is a significant consumer of water and produces huge amounts of contaminated water. The dyes and pigments present in wastewater make industrial effluents very hazardous due to their toxicity, cause low biodegradability and affect the colour intensity of water. The content of dyes in surface water negatively affects the entire ecosystem by interfering with the correct photosynthetic process. In addition, the content of dyes in water has harmful effects on living organisms, including the human body. They can cause various diseases. The aim of this study was to investigate the removal of selected dyes from aqueous solutions. The sorption under flow conditions of two dyes, a cationic dye (anilan red) and an anionic dye (acid amaranth) on activated carbons ROW 08 Supra and WG-12 was studied. The flow direction of the solution containing the dye solution was from top to bottom with flow velocities of 3, 6 and 9 m/h. Tests were carried out until a dye concentration equal to 0.9 of the initial concentration was obtained in the column effluent. Based on the laboratory results obtained, so-called exit curves were plotted. Dynamic dye adsorption values were high, especially for ROW 08 Supra activated carbon. Of the activated carbons used in the study, the most efficient adsorption under dynamic conditions took place on ROW 08 Supra activated carbon. The longest times to complete depletion of the sorption capacity were obtained on this activated carbon.